An overview of cement tile manufacturing and importation in Syria and Lebanon: Damascus-Beirut, 1880s-1940s - Anas Soufan (ABE Journal)
Cement tiles are an instance of the new materials of construction that characterized the architecture of Modernity in Syria and Lebanon beginning in the late nineteenth century. The introduction of this material, widespread during the colonial and post-colonial periods, goes back to the 1880s. It was an effect of major upheavals that struck Syrian society in the wake of the Egyptian expedition (1831-1840). Undoubtedly, this material influenced interior design, offering a new understanding of material and color and, subsequently, a new appropriation of the interior space. Indeed, the cement tiles, whose span extended to all the Mediterranean shores, created a supplementary expression of their artistic and cultural interconnectivities. This investigation into the importation and local manufacturing of this material raises not only technical aspects but also the general context that affected building activities during the period under review. Therefore, this survey’s analyses and conclusions seek to articulate the impact of the esthetic, industrial, and commercial characteristics of the cement tiles, as well as the historic dimension of their employment, the Syrians’ tendency toward imitation and renewal, the acceleration of contacts with Europe, and transformations in the ways of production and consumption. Although cement tiles were for decades the most widely utilized floor covering material in Syria and Lebanon, its importation and local manufacturing have not been the thrust of specialized investigations. Only a few related themes have been approached by scholars such as Robert Saliba and ‘Ādel Sṭās and by architects such as Sophie Skaf, who developed a notable inventory of widespread models in Beirut–and other cities–during the first half of the twentieth century. Thus, the aim of our survey is to build on previous work and to propose an established historiography of the importation and the local manufacturing of cement tiles in a defined temporal and geographical framework: Damascus and Beirut, from the 1880s to the 1930s.